Long-Run Commodity Prices, Economic Growth, and Interest Rates: 17th Century to the Present Day. (January 2017) - Harvey, David I.; Kellard, Neil M.; Madsen, Jakob B.; Wohar, Mark E.
Highlights: Examines commodity prices, income, and interest rates over the long-run. Prices present a downward trend with breaks while income trends upward with breaks. Prices Granger cause income and interest rates, while interest rates cause prices. Implications for the Prebisch–Singer hypothesis, resource curse, and monetary policy. Summary: A significant proportion of the trade basket of many developing countries is comprised of primary commodities. This implies relative price movements in commodities may have important consequences for economic growth and poverty reduction. Taking a long-run perspective, we examine the historical relation between a new aggregate index of commodity prices, economic activity, and interest rates. Initial empirical tests show that commodity prices present a downward trend with breaks over the entire industrial age, providing clear support for the Prebisch–Singer hypothesis. It would also appear that this trend has declined at a faster rate since the 1870s. Conversely, several GDP series such as World, Chile, China, UK, and US, trend upward with breaks. Such trending behavior in both commodity prices and economic activity suggests a latent common factor like technological innovation. To assess the relationships between economic series, we apply a stationary VAR (Vector Autoregression) to model movements around trends. Strikingly, there is evidence that commodity prices Granger cause income and interest rates, while interest rates Granger cause commodity prices. From these results and the related impulse response function analysis, the historical perspective provides some useful information for contemporary policy makers. For example, loose monetary policy has tended to support higher commodity prices. Moreover, commodity price movements have an asymmetric country effect on economic activity; periods of falling commodity prices will support GDP growth for commodity importers like the US but depress growth for commodity exporters such as Chile.